Secondary neutrons in proton and light ion beam therapy: a review of current status, needs and potential solutions - Vedelago, José; Schmidt, Stefan; Stengl, Christina; Karger, Christian; Jäkel, Oliver (Radiation measurements, 2024)
The advantages of proton and light ion beam therapy compared to conventional photon radiation therapy are well-known, mainly thanks to the characteristic depth dose distribution of ions and their radio-biological effectiveness. Nevertheless, the use of ions implies different nuclear reactions that generate secondary particles, with neutrons among them. These secondary neutrons can travel far away from the treatment volume, their measurement is a challenging complex task, and their biological effects are particularly high for neutrons with energies in the MeV range. In this review, a comprehensive description of secondary neutron dosimetry in proton and light ion beam therapy is given. Many studies have been conducted on the quantification of the secondary neutron dose, most of them have been performed for proton beams, whereas for other ions like carbon, the available information is scarce. The main measurement campaigns are summarised, focusing on the type of detectors used. In line with the detectors’ advantages and limitations, measurements performed inside and outside anthropomorphic phantoms are considered. The role of Monte Carlo radiation transport simulations is discussed since many experimental detection techniques need additional simulations to provide dose estimates. A focus on the current challenges for the measurements of neutrons with energies above 20 MeV is given, as this is one of the main components of secondary neutrons produced by therapeutic ion beams. Finally, the potential clinical relevance of the available and needed secondary neutron dose data is discussed, in terms of its impact on the treatment of patients. For this, the relative biological effectiveness of neutrons and the potential risk of cancer induction re-incidence or secondary cancer due to secondary neutron doses play a key role.